The effect of different irrigation activation techniques on smear layer removal, bioceramic sealer penetration, and interfacial adaptation: SEM and CLSM evaluation - Maryam Saber Mahdi; Ranjdar Mahmood Talabani (PLoS ONE, 2025)
Background The success of endodontic treatment relies on the cleaning, disinfection, and sealing of the root canal system. This study evaluated the effects of four different irrigation techniques on smear layer removal, dentinal tubule penetration, and interfacial adaptation of a bioceramic root canal sealer. Method Eighty-four sound single-rooted lower premolars were decoronated, prepared to medium size WaveOne Gold reciprocating files, and divided randomly into four groups: group I conventional needle irrigation, group II heat activation, group III Diode laser activation, and group IV XP-endo Finisher file activation. Half of the samples (n = 40) were used to assess smear layer removal, while the other forty-four teeth were used to measure the sealer’s penetration and interfacial adaptation after obturation with Bio_C sealer and gutta-percha; the assessments were done using scanning electron microscopy (SEM) and confocal laser scanning microscope (CLSM). Results No statistically significant differences were found between irrigation activation groups related to smear layer removal assessment (p-value>0.05), while the XP-endo Finisher file activation group showed significantly the highest sealer penetration in the apical third, and the best adaptation in the middle third. Conclusion Irrigation activation can enhance the penetration of the sealer and interfacial adaptation.